When and how does counterfactual thinking prevent catastrophes and foster group decision accuracy. Issue 2 (11th April 2016) - Tripathi, Mamta; Nath Srivastava, Bharatendu
Abstract : Purpose: The purpose of the paper is to develop a theoretical framework with testable propositions discussing the role of counterfactual thinking in fostering accurate decision-making in groups and preventing catastrophes, being mediated by information searching, sharing, task conflict and conflict management mechanisms, moderated by task complexity, cognitive complexity, cognitive closure and tolerance of ambiguity. Design/methodology/approach: A theoretical framework is formulated and propositions are postulated involving independent, mediating, moderating and dependent variables. Findings: This paper recommends a helpful framework for understanding of how counterfactual thinking affects information searching, sharing and decision-making accuracy in groups, thereby preventing catastrophes. Practical/implications: The proposed framework might be of assistance in managing complex group decision-making and information sharing in organizations. Decision-makers may become aware that activating counterfactual mind-set enables them to search for critical information facilitating accurate decision-making in groups leading to catastrophe prevention. Originality/value: This paper adds value to the field of counterfactual thinking theory applied to group decision-making. Moreover, the paper provides a novel framework for group decision-making which sheds light on pertinent variables, which can either ameliorate or exacerbate the accuracy of decision-making by information searching and sharing in groups under varying context of high/low task complexity. The ramifications of task conflict, conflict management mechanisms, team diversity and size are explored alongside the moderating role of cognitive complexity, cognitive closure and tolerance for ambiguity.